Experimental and theoretical study of the two-phase flow inside a lean premixed prevaporised combustor - Monmont, Franck (Cranfield University, 1999)
A experimental study of the two-phase flow inside a lean premixed prevaporised combustor has been carried out in order to evaluate the capabilities of large eddy simulations applied to engineering applications. To this end, a existing LPP design was modified in order to simplify the injection mechanisms involved and gain a optimum optical access if the critical injection region. The liquid and the gas phase inside the LPP module are then characterised with the help of non-invasive laser techniques, namely PDA for the liquid phase, LDA for the airstream and PLIF for the vapour phase. Relevant information regarding droplet sizes, droplet velocity, airstream velocity and fuel placement have thus been collected. The measurements are then evaluated against flow solutions computed by a Eulerian-Lagrangian ite-volume solver. A hybrid RANS/LES modelling strategy has been adopted for the gas phase and the Lagrangian tracking procedure has been updated to predict the influence of the gas turbulence on the droplet dispersion, and the heat penetrating the droplet during its evaporation. This simulation is finally matched against ZD and 3D steady RANS solution in a attempt to demonstrate the superiority of the time dependent approach.